Perancangan Pembangkit Listrik Tenaga Hibrida (PLTS Dan PLTMH-GRID) Di Desa Tiworiwu I Dan Desa Bea Pawe, Kabupaten Ngada, Nusa Tenggara Timur (NTT) - Mardelin Kastela; Widodo, Bambang; Purba, Robinson (Prodi Teknik Elektro FT UKI, 2023)
Tiworiwu I Village and Bea Pawe Village, located in Ngada Regency, have a renewable energy power plant, the Wae Roa Microhydro Power Plant (PLTMH), which is connected to PLN. The total power capacity generated from this power plant reaches 370 kW and the location of the plant is in Bea Pawe Village. This research was conducted with the aim of designing a Hybrid Power Plant (PLTH) by combining PLTMH-Grid and Solar Power Plant (PLTS). The level of solar radiation in Bea Pawe Village reached 5,531 kWh/m2. Thecapacity of the solar module used in this study was 325 Wp/module. The total total capacity reaches 525,200 Wp with the number of Photovoltaic (PV) modules as many as 1616 units and 53 inverter units with a capacity of 10 kW, so that the total inverter capacity reaches 530 kW. After conducting a simulation analysis of PLTH using HOMER software, it shows that the production of electrical energy produced by PLTH in Tiworiwu I Village and Bea Pawe Village is 3,131,745 kWh / year. The contribution of PLTS in energy production is 27.5%, the contribution of PLTMH is 51.5%, and the contribution of the electricity network (grid) is 21%. From an economic point of view, the estimated Net Present Cost (NPC) value of PLTH is much lower than that of PLTMH-Grid, with a difference of Rp. 5,304,430,000. Levelized Cost of Electricity (LCOE) at PLTMH-Grid is also lower, with a difference of Rp. 383.39 / kWh. Break Even Point (BEP) is expected to occur in about 5.05 years. The NPC and LCOE values of PLTH are lower than PLTMH-Grid PLN.